Mitigating effects of Jambul against lead induced toxicity in epididymis and vas deferens of mice - Tahir Abbas; Khawaja Raees Ahmad; Asmat Ullah; Samreen Iqbal; Kausar Raees (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Precious fruits like jambul are neglected and wasted while environmental pollutants like lead intake remain overlooked. Objective: The aim of this study was to investigate the effects of the Jambul pulp extract on lead detrimental effects in pseudostratified epithelium and the stereocilia of mice epididymis and vas deferens. Materials and Methods: Thirty young males mice (Mus musculus) were distributed randomly in 3 groups (n= 10) called control, Pb (Lead) and Pb-J (Lead-Jambul). The Pb and Pb-J were provided 50ppm Pb in drinking water ad libitum for 15 days and Pb free water for the next 5 days. The Pb-J group received 0.2ml jambul pulp extract on 12 hourly bases. Control group was not given any treatment. Organs (epididymis and vas deference) were recovered on 21st day after euthanasia. The organs were finally processed for histological and micrometric studies. Results: Marked histologic and micrometric changes in both organs were noted in Pb group. These include significant (P ≤ 0.05) decrease in cross sectional area of caput and cauda epididymis folding tubing along with evident alterations of their endothelial thickness. Prominent signs of apoptosis (vacuolations) in the corpus pseudostratified endothelium and the destruction of stereocilia of the epididymis and vas deferens in Pb compared to control group were observed. Evident signs of recovery, in both organs, such as proliferation and rearrangements in pseudostratified endothelium and the stereocilia along with convincing recovery in micrometric parameters were observed in Pb-J group. Conclusion: The results indicate that epididymis and vas deferens are highly sensitive to Pb exposure while Jambul pulp extract has shown rich mitigating potentials against such histopathologies.